Tingkat Pengetahuan Siswa Sekolah Menengah Atas Terhadap Keselamatan dalam Pembelajaran Bola Basket di Masa Covid 19 - Riki Hermawan; Rina Marlina; Febi Kurniawan (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine whether the level of students' knowledge of safety in students' basketball learning could increase students' knowledge of basketball learning in SMA 1 Sukatani class X SMA 1 Sukatani. This study was a descriptive study. Descriptive research is a research conducted to describe certain symptoms, phenomena or events (Maksum, 2012: 68). By using a quantitative approach. Researchers just want to know how the actual events in the field. In this study, the survey method was used with data collection techniques using questionnaires. From the results of the study, it is known that the level of knowledge of high school students on safety in basketball learning during the Covid 19 class X SMA 1 Sukatani, which stated the category "very high" with a percentage of 0%, the category "high" with a percentage of 30%, category " medium" with a percentage of 43%, the "low" category with a percentage of 19%, and the "very low" category with a percentage of 8%. good or moderate category.